Protecting Cyber Crime Victims: Trends and Imperatives in Legal Safeguards - Lestari, Lusiana; Rosnawati, Emy; Fidayanti, Anita Rohma (Proceedings of The ICECRS, 2023)
This data article presents an analysis of 10,446 scholarly articles on Crime Victims within Cyber Law sourced from Lens.org. Using rigorous filtering, the dataset unveils key contributors and trends, notably a surge in publications in 2017 and the dominance of the Law field. The findings emphasize the pressing need for enhanced legal safeguards to protect Crime Victims in cyberspace, serving as a foundation for policy reform and further academic inquiry. Highlights : Surge in Publications: Sharp increase in articles in 2017 highlights growing attention to cyber law and crime victimization. Dominance of Law Field: Emphasis on legal aspects underscores the need for legal frameworks in addressing cybercrime against victims. Call for Action: Findings stress the urgency for improved safeguards and policy reforms to protect victims in cyberspace. Keywords: Crime Victims, Cyber Law, Legal Safeguards, Policy Reform, Academic Inquiry